2022
DOI: 10.1038/s41598-022-05264-1
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood spot sampling for hepatitis B virus quantification, sequencing and mutation detection

Abstract: Hepatitis B virus (HBV) diagnosis is performed on serum samples, but the access to this diagnosis is difficult in low-income regions. The use of dried blood spot (DBS) samples does not require special structure for collection, storage or transport. This study evaluates the use of DBS for detection, quantification and sequencing of HBV DNA using in-house techniques. Two study groups were included: 92 HBsAg + individuals and 49 negative controls. Serum and DBS samples were submitted to quantitative and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Notably, one study ( n = 1) investigated individuals occupationally exposed to BBVs, specifically hairdressers 82 . It is important to mention that six studies did not specify the population from which the samples were taken 83–88 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, one study ( n = 1) investigated individuals occupationally exposed to BBVs, specifically hairdressers 82 . It is important to mention that six studies did not specify the population from which the samples were taken 83–88 …”
Section: Resultsmentioning
confidence: 99%
“…82 It is important to mention that six studies did not specify the population from which the samples were taken. [83][84][85][86][87][88]…”
Section: F I G U R Ementioning
confidence: 99%
“…HBV antigen, antibodies and DNA could be detected by EIA and PCR method in DBS and the diagnostic accuracy and precision have been confirmed by many studies ( 61 , 62 ). In 2022, the applicability of DBS for sequencing, as HBV genotyping and tracking mutations was evaluated ( 63 ). The 2017 WHO Guidelines recommended that DBS should be considered for serological and nucleic acid testing HBV and HCV technologies where laboratory detection is not available or when patients showed poor venous access ( 8 ).…”
Section: Diagnose Hbv Using Dried Blood Spotmentioning
confidence: 99%
“…Previous studies have demonstrated the applicability of dried blood spot (DBS) and oral fluid samples as convenient alternatives for HBV detection and sequencing 6 , 7 . They are less invasive, easier to collect, require minimal training and may be useful for accessing HBV diversity in settings where blood collection is difficult.…”
Section: Introductionmentioning
confidence: 99%